MicroRNA miR-BART20-5p Stabilizes Epstein-Barr Virus Latency by Directly Targeting BZLF1 and BRLF1 - Jung, Yu-Jin (American Society for Microbiology, 2014)
Epstein-Barr virus (EBV) is a human herpesvirus associated with various tumors. Rather than going through the lytic cycle, EBV maintains latency by limiting the expression of viral genes in tumors. Viral microRNAs (miRNAs) of some herpesviruses have been reported to directly target immediate early genes and suppress lytic induction. In this study, we investigated whether BamHI-A rightward transcript (BART) miRNAs targeted two EBV immediate early genes, BZLF1 and BRLF1. Bioinformatic analysis predicted that 12 different BART miRNAs would target BRLF1. Of these, the results of a luciferase reporter assay indicated that only one interacted with the 3′ untranslated region (UTR) of BRLF1: miR-BART20-5p. miR-BART20-5p's effect on gene expression involved two putative seed match sites in the BRLF1 3′ UTR, but a mutant version of the miRNA, miR-BART20-5pm, had no effect on expression. As expected from the fact that the entire 3′ UTR of BZLF1 resides within the 3′ UTR of BRLF1, miR-BART20-5p interacted with the 3′ UTR of BZLF1 as well. BZLF1 and BRLF1 mRNA and protein expression was suppressed in cells of an AGS cell line infected with the recombinant Akata strain of EBV (AGS-EBV) transfected with a miR-BART20-5p mimic. The expression of various EBV early proteins was also suppressed by the miR-BART20-5p mimic. In contrast, BZLF1 and BRLF1 expression in AGS-EBV cells transfected with a miR-BART20-5p inhibitor was enhanced. Furthermore, progeny virus production was suppressed by the miR-BART20-5p mimic and enhanced by the miR-BART20-5p inhibitor in AGS-EBV cells induced for the lytic cycle. Our data suggest that miR-BART20-5p plays a key role in latency maintenance in EBV-associated tumors by directly targeting immediate early genes. IMPORTANCE Herpesviruses maintain latency using various mechanisms and establish lifelong infection in the host. From time to time, herpesviruses are reactivated and express immediate early genes which trigger a lytic cascade, leading to the production of progeny viruses. Recently, some herpesviruses have been shown to use their own microRNAs (miRNAs) to downregulate immediate early genes to inhibit the lytic cycle. This study presents evidence that EBV also downregulates two immediate early genes by miR-BART20-5p to suppress the lytic cycle and progeny virus production. Overall, this is the first study to report the direct regulation of EBV immediate early genes by an EBV miRNA, implying its likely importance in latency maintenance in EBV-associated tumors.